1968: In Search of “Socialism with Human Face” in Czech Art History - Bartlová, Milena (Artium Quaestiones, 2019)
The five or eight years leading up to the failed “Prague Spring” represent the most important period of Czech humanities tradition during the Communist Party dictatorship. Art history did not directly participate in either of the most prominent period discourses, but it was able to develop its own specific methodologies following the Czech continuation of the Vienna School legacy. The contribution analyzes the discourse of Marxist Iconology, developed by J. Neumann and R. Chadraba, and presents the case of F. Šmejkal and his concept of Imaginative Art, which was, interestingly, the sole case during the whole 40 years of the Communist Party rule when the highest Party officials became directly involved in Czech art historical practice. From the point of view of art historical practice, the most important feature of the brief period 1963–1969 was the new possibility of contacts with foreign art historians and of traveling abroad.